2015
DOI: 10.1371/journal.pone.0125946
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis Underlying the Binding Preference of Human Galectins-1, -3 and -7 for Galβ1-3/4GlcNAc

Abstract: Galectins represent β-galactoside-binding proteins and are known to bind Galβ1-3/4GlcNAc disaccharides (abbreviated as LN1 and LN2, respectively). Despite high sequence and structural homology shared by the carbohydrate recognition domain (CRD) of all galectin members, how each galectin displays different sugar-binding specificity still remains ambiguous. Herein we provided the first structural evidence of human galectins-1, 3-CRD and 7 in complex with LN1. Galectins-1 and 3 were shown to have higher affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 45 publications
6
45
1
Order By: Relevance
“…This detection failure was most likely due to the intrinsic limitation of the BLI method, similar to that of SPR. Increasing Gal-3 immobilization with a super streptavidin sensor (SSA) may increase oligosaccharide binding and thus increase instrument response [39]. Although galactan immobilization on the sensor is an alternative, this is not easily performed as discussed in the case of SPR.…”
Section: Biolayer Interforometory (Bli)mentioning
confidence: 99%
“…This detection failure was most likely due to the intrinsic limitation of the BLI method, similar to that of SPR. Increasing Gal-3 immobilization with a super streptavidin sensor (SSA) may increase oligosaccharide binding and thus increase instrument response [39]. Although galactan immobilization on the sensor is an alternative, this is not easily performed as discussed in the case of SPR.…”
Section: Biolayer Interforometory (Bli)mentioning
confidence: 99%
“…In the case of lactose, its K d values for hGal1, hGal7 and the hGal8 N-terminal domain (hGal8 NTD ) and C-terminal domain (hGal8 CTD ) can vary by more than an order of magnitude without appreciable structural differences in the residues that are in direct contact with lactose, according to crystallographic analyses ( Figure 1 ). A recent structural study indicated that the substrate binding preference may be associated with a salt bridge between the two ends of the loop on which a conserved arginine side-chain for carbohydrate binding is located [ 24 ], suggesting that structural and/or dynamics changes away from the direct contacting residues may play an important role in substrate recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Going from lactose to LacNAc results in a 5-fold weaker binding, but then changing from LacNAc to incorporate a β1,3-linkage results in an affinity that is just 2-fold weaker than lactose and ~2.6-fold stronger than for LacNAc. Conformation of the type 1 core disaccharide (Type 1 N- Acetyl-lactosamine) bound to galectin-1 (4XBL40), galectin-3 (4XBN40) and galectin-7 (4XBQ40), observed in crystal structures, also reveal an identical placement of the galactose ring, whereas the slight variation in the glycosidic torsional angle between the two rings results in different GlcNAc orientation. Given the higher average B-factor for GlcNAc (~19 Å 2 ) as compared to the galactose ring (~14 Å 2 ) observed in our structure, which is a similar trend to other galectin-glycan complexes, overall the binding conformation of the type 1 core appears to be comparable throughout the galectin family.…”
Section: Resultsmentioning
confidence: 98%